Progress in the development and application of CaO-based adsorbents for CO2 capture—a review. (December 2018) - Sun, H.; Wu, C.; Shen, B.; Zhang, X.; Zhang, Y.; Huang, J.
Abstract: Carbon dioxide (CO2 ) capture using CaO-based adsorbents has recently attracted intense attention from both academic and industrial sectors in the last decade due to the high theoretical capacity of CO2 capture, low cost, and potential use in large scale. However, the successful development of CaO-based adsorbents is limited by significant sintering of adsorbent particles over a number of cycles of CaO carbonation/calcination. In this work, a systematic understanding of fundamental aspects of the cyclic carbonation/calcination of CaO-based materials is reviewed. A number of efforts have been discussed to improve the sintering-resistant properties of CaO-based adsorbents, such as decreasing the particle size and increasing the surface area, dispersing CaO on inert support, as well as surface modification. In particular, severe process conditions such as carrying out material calcination under pure CO2 atmosphere were considered for the development of CaO-based materials. In addition, important process parameters for CaO-based carbon capture such as CO2 partial pressure, carbonation temperature, carbonation time and the presence of contaminants have been reviewed, as well as the reactivation of spent sorbents. Synthetic CaO-based adsorbents have better performance than natural adsorbents due to the improved porosity and the presence of nanosized particles. The promising capacity and stability of CO2 capture can be obtained when the synthetic adsorbents have high surface area and mesopores and/or CaO particles are stabilized using inert materials such as Ca12 Al14 O33 . With an increase of steam concentration in the process, the decay of CO2 capture capacity was mitigated due to the formation of a stable pore structure. The calcium looping technology has been demonstrated in pilot scale combining with catalytic reforming or gasification process. However, the reduction of sorbent costs and the optimization of process conditions (e.g. carbonation and calcination time) still need to be tested in larger scale to reduce the overall costs and enhance the overall energy efficiency. Material attrition is a key challenge in large-scale demonstration of calcium looping process. Novel technology could be developed to avoid the transportation of solid sorbents. For example, by integrating with CO2 conversion to methane, the capture of CO2 and the regeneration of bifunctional sorbents can be carried out at the same temperature in a fixed bed reactor. This can be fulfilled by introducing hydrogen to the stage of sorbent regeneration. However, much more fundamental understanding is required in this area, such as the exploration of synergies between sorbent regeneration and catalytic conversion of CO2 . Graphical abstract: Image 1